Growth, Laying Performance, and Egg Quality of White Leghorn Chickens Supplemented with Live Black Soldier Fly (Hermetia illucens) Larvae Under Litter Floor Rearing System - Emelyn D. Tormes; Jodie Mer C. Dayama (Future Science / FSH-PH Publications, 2026)
This study was conducted in Mati, San Miguel, Zamboanga del Sur to evaluate the growth performance, laying performance, and egg quality of White Leghorn chickens supplemented with Black Soldier Fly Larvae (BSFL) under a litter floor rearing system using a Completely Randomized Design (CRD). Sixty (60) ready-to-lay chickens were randomly assigned to four treatments with three replications of five birds each. Treatment 1 received 100% commercial feed, while Treatments 2, 3, and 4 were supplemented with 15%, 20%, and 25% BSFL, respectively. Data collected included average daily gain, feed intake, feed conversion ratio (FCR), egg production, hen-day egg production, egg weight, egg size (length and width), shape index, yolk diameter and height, yolk index, and yolk color. All data were analyzed using Analysis of Variance (ANOVA) through the Statistical Tool for Agricultural Research (STAR). Results revealed that growth performance (average daily gain, feed intake, and FCR) exhibited only numerical differences and was not statistically significant (p > 0.05) among treatments. However, laying performance and egg quality showed high statistical significance (p < 0.01). Chickens supplemented with 20% BSFL (T3) recorded the highest egg production, hen-day egg production, egg weight, egg size, and improved FCR for egg production. Economic analysis indicated that 20% BSFL supplementation provided the most cost-effective return.